Respuesta :

Answer:

(-1,3) is a SOLUTION Of the inequality y > 4 x  - 9.

(0,-9) is NOT a SOLUTION Of the inequality y > 4 x  - 9.

(1,0) is a SOLUTION Of the inequality y > 4 x  - 9.

(2,1) is a SOLUTION Of the inequality y > 4 x  - 9.

Step-by-step explanation:

Here, the given inequality is: y > 4 x  - 9

Now, to show if the ordered pair are solutions, SUBSTITUTE each pair in the equation:

(a) (-1,3)

Here, substitute x  =   -1 and y = 3 in  y > 4 x  - 9

We get:  3 > 4(-1) - 9  

or, 3 > -13  ( THIS INEQUALITY is TRUE)

⇒ (-1,3) is a SOLUTION Of the inequality y > 4 x  - 9.

(b) (0,-9)

Here, substitute x  =  0 and y = -9 in  y > 4 x  - 9

We get:  -9 > 4(0) - 9  

or, -9 > -9  ( THIS INEQUALITY is NOT TRUE)

⇒ (0,-9) is NOT a SOLUTION Of the inequality y > 4 x  - 9.

(c) (1,0)

Here, substitute x  =  1 and y = 0 in  y > 4 x  - 9

We get:  0 > 4(1) - 9  

or, 0 > -5  ( THIS INEQUALITY is TRUE)

⇒ (1,0) is a SOLUTION Of the inequality y > 4 x  - 9.

(d) (2,1)

Here, substitute x  =  2 and y = 1 in  y > 4 x  - 9

We get:  1 > 4(2) - 9  

or, 1 > -1  ( THIS INEQUALITY is TRUE)

⇒ (2,1) is a SOLUTION Of the inequality y > 4 x  - 9.

ACCESS MORE